Geochemical and mineralogical heterogeneity of the Cantung mine tailings: implications for remediation and reprocessing - Surrette, A.; Dobosz, A.; Lambiv Dzemua, G.; Falck, H.; Jamieson, H. E. (Frontiers in Geochemistry, 2024)
Reprocessing tailings to recover minerals of economic interest and environmental concern can add value to a project and decrease environmental risk, but dealing with heterogeneity within tailings facilities is a challenge. This study investigates the heterogeneity of the Cantung Mine tailings to assess the potential for reprocessing for both value recovery and remediation purposes. The Cantung Mine, Northwest Territories, was a world-class tungsten (W) deposit that was mined periodically from 1962 to 2015. Geochemical analysis of 196 tailings samples shows substantial heterogeneity in the elements of value (tungsten and copper (Cu)) and elements of environmental concern for acid rock drainage (iron (Fe) and sulfur (S)). Tungsten and copper concentrations range from 0.06 to 1.06 wt.% W (average 0.32 wt.% W) and 0.05 to 0.48 wt.% Cu (average 0.23 wt.% Cu). Iron and sulfur concentrations range from 8.25 to 34.08 wt.% Fe (average 17.14 wt.% Fe) and 2.20 to 19.70 wt.% S (average 6.7 wt.% S). Characterization of 29 samples by scanning electron microscope with automated mineralogy software shows that geochemical heterogeneity corresponds to mineralogical heterogeneity with variability in the concentrations of scheelite (CaWO4), chalcopyrite (CuFeS2) and pyrrhotite (Fe(1-x)S). Liberation analyses indicate that additional grinding would be necessary to recover scheelite, chalcopyrite or pyrrhotite. Pyrrhotite with monoclinic and hexagonal-orthorhombic forms were identified. Overall, the Cantung tailings display considerable heterogeneity, which could lead to difficulties in reprocessing for economic or environmental benefit, but characterizing the heterogeneity allows for systems to be optimized.